A legal study on the necessity of recognising transsexualism in Malaysia / Mohd Azri Mohamad Ghazali …[et al.] - Mohamad Ghazali, Mohd Azri; Mohd Ariffin, Nik Nurezzah; Abd Talib, Noor Raihan; Zulkipli, Sara Afiqah; Mustaffa, Tarmizi (2010)
Transgender and their rights have been a contentious issue in Malaysia due to the nonrecognition of their status in our legal system. Hence, transgender community face hardship and discrimination and they often are segregated from the society. The purpose of our research is to examine the necessity of having specific regulations that recognises the transgender community in Malaysia pertaining their legal position, their social liberties and their equal chance at employment and to observe their situation in other countries. This project paper had explored the opinion of legal practitioner and religious expert, the view of the transgender community itself, the practice in other countries and the acceptance of the Malaysian community towards their legal status. Based on our research, we have found that to constitute the legal status of the transgender, society's perception and acceptance play an essential part. If the society is not yet ready for the change, legalising the status of transgender will serve no purpose. Therefore, several suggestions are proposed to counter this issue. They include reviewing any law that is discriminatory towards the transgender, equal opportunity to transgender in terms of the employment, education and sensitivity of the government authorities.